Obesity indices and diabetes risk among hypertensive patients: insights from the China Multi-Ethnicity Cohort study - Zhou, Enhui; Hong, Feng (Frontiers in Endocrinology, 2025)
BackgroundThe atherogenic index of plasma (AIP) is recognized as a surrogate marker for dyslipidemia. It has been well-established that the AIP is significantly associated with diabetes, and obesity is a known risk factor for both dyslipidemia and diabetes. However, the relationship between obesity and diabetes, as well as the potential role of the AIP in hypertensive minority populations, remains unclear. This study aimed to assess the association between obesity index and diabetes in hypertensive people.Methods and resultsThis cross-sectional study included 9,446 participants from the China Multi-Ethnicity Cohort (CMEC) study. Our study suggested that obesity indices were significantly higher in diabetic patients compared to those without. Moreover, logistic regression analysis suggested that higher quartiles of obesity indices were associated with an increased risk of diabetes whether in crude or adjusted models (p < 0.05). Mediation analysis revealed that the association between obesity and the risk of diabetes, mediated by body mass index (BMI), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), and body adiposity index (BAI), through the AIP was 17.2%, 15.3%, 15.8%, and 19.2%, respectively. Additionally, restricted cubic spline analysis revealed a non-linear relationship between obesity indices and diabetes.ConclusionIn summary, obesity is significantly associated with diabetes in hypertensive minority Chinese, with the AIP partially mediating this relationship.